STRATEGI PENGEMBANGAN UMKM DALAM MENINGKATKAN DAYA SAING INDUSTRI BATIK DI KOTA BANDAR LAMPUNG - Shella Oktaviana; Sarah Aqila; Nadira Dwita Anggraini; Nia Kurniasih; Rahma Dini; Nunur Oktavianti; Ima Andriyani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving regional economic growth, creating employment opportunities, and preserving cultural heritage through the development of the batik industry. However, the increasing level of competition in the batik industry requires every business actor to have appropriate development strategies in order to enhance competitiveness and maintain business sustainability. Griya Batik Gabovira, as one of the MSMEs in Bandar Lampung City, faces various challenges, such as competition with batik products from other regions, changes in consumer preferences, and the development of marketing technology. This study aims to analyze the development strategies implemented by Griya Batik Gabovira in enhancing the competitiveness of the batik industry. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, documentation, and literature studies. The results show that the development strategies implemented include improving product quality, innovating batik motifs that promote local Lampung culture, developing human resource competencies, utilizing digital media as a marketing tool, and expanding collaboration networks through various promotional activities and exhibitions. The implementation of these strategies has been able to increase product added value, expand market share, and strengthen business competitiveness amid the increasingly competitive batik industry. Therefore, continuous innovation and the ability to adapt to changing market needs are important factors in supporting the sustainability and competitiveness of the MSME Griya Batik Gabovira.